Are nudging and pricing strategies on food purchasing behaviors equally effective for all? Secondary analyses from the Supreme Nudge virtual supermarket study. (1st December 2021) - van der Molen, Annemarijn E.H.; Hoenink, Jody C.; Mackenbach, Joreintje D.; Waterlander, Wilma; Lakerveld, Jeroen; Beulens, Joline W.J.
Abstract: Nudging and pricing strategies are effective in promoting healthier purchases. However, whether the effects are equal across individuals with different personal characteristics is unknown. This exploratory study aimed to examine differential effects of nudging and pricing strategies on food purchases across individuals' levels of impulsivity, price sensitivity, decision-making styles, and food choice motives. Data from a virtual supermarket experiment where participants were exposed to five study conditions (control, nudging, pricing, salient pricing, and salient pricing with nudging) was used. Participants completed questionnaires assessing their impulsivity, price sensitivity, decision-making styles, and food choice motives. The outcome was the percentage of healthy food purchases. Effect modification was analyzed by adding interaction terms to the statistical models and post-hoc probing was conducted for statistically significant interaction terms. We used data from 400 Dutch adult participants (61.3% female, median age 30.0 years (IQR 24.0)). The effects of the nudging and pricing conditions on healthy food purchases were not modified by impulsivity, price sensitivity, decision-making styles, and the food choice motives 'health' and 'price'. Only the interactions of the food choice motive 'natural content of foods' x pricing (B = −1.02, 90%CI = −2.04; −0.01), the food choice motive 'weight control' x nudging (B = −2.15, 90%CI = −3.34; −0.95), and 'weight control' x pricing (B = −1.87, 90%CI = −3.11; −0.62) were statistically significant. Post-hoc probing indicated that nudging and/or pricing strategies were more effective in individuals who gave lower priority to these food choice motives. The effects of nudging and pricing strategies on increasing healthy food purchasing behaviors, at least in a virtual environment, do not seem to be influenced by personal characteristics and may therefore be implemented as general health promoting strategies.